2012
DOI: 10.1177/1040638711435141
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a gamma interferon release assay in the diagnosis of naturally infected pigs with Mycobacterium avium subspecies hominissuis

Abstract: In the current study, the results of an intradermal tuberculin test and a gamma interferon (IFN-γ) release assay were compared. IFN-γ release assay is based on the detection of IFN-γ production after in vitro stimulation with Mycobacterium avium subsp. avium-specific antigen for the discrimination of pigs naturally infected with M. avium subsp. hominissuis. Fiftyfive clinically healthy pigs were used in the study. Three of these were proven by culture and real-time quantitative polymerase chain reaction method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Joint research of Norwegian and Serbian researchers has found that the use of bovine and aviary tuberculin increases the detection sensitivity to mycobacteria, including members of MAC. A reaction to both types of tuberculin is common although only MAH was detected [53,56].…”
Section: Mac Diagnostics -Main Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joint research of Norwegian and Serbian researchers has found that the use of bovine and aviary tuberculin increases the detection sensitivity to mycobacteria, including members of MAC. A reaction to both types of tuberculin is common although only MAH was detected [53,56].…”
Section: Mac Diagnostics -Main Pointsmentioning
confidence: 99%
“…Intradermal tuberculin test and gamma interferon tests are the only methods that can be used for live animals. Unfortunately, the use of tuberculin skin test in the majority of EU countries has not been mandatory for many years, while the use of gamma interferon test in swine production is only used mostly for research purposes [56]. Although imperfect, the tuberculin test is a cheap method that has signifi cantly contributed to the eradication of tuberculosis in cattle and consequently in humans [65].…”
Section: Mac Diagnostics -Main Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other mycobacteria, such as members of the Mycobacterium avium complex (MAC), lead to a granulomatous lymphadenitis (GL)in head and mesenteric lymph nodes that, despite its economic importance due to the condemnation of carcasses (Faldyna et al 2012), present a lower public health risk, often restricted to immunocompromised people.…”
Section: Introductionmentioning
confidence: 99%
“…Although serological assays have been developed with promising results (Boadella et al 2011, Wisselink et al 2010, as well as an Interferon-gamma release assay (Faldyna et al 2012), they are mainly focused on the diagnosis of lymphadenitis, which is determined by MAC. To our knowledge, there are no studies addressing the diagnosis of M. bovis infections in swine and/or designed to discriminate between infections determined by M. bovis or MAC.…”
Section: Introductionmentioning
confidence: 99%